Las hebras para hilvanar la vida: el dibujo del dolor - Hernández Merino, Ana (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
Here is commented an exhibition about the drawings of th children in the Spanish civil war. From it, some aspects are checked concerning the birth of the art as therapy and concerning the children’s drawing, specifi cally Winnicot’s contributions on special situations as the war. Finally, Regina Lago’s work in the epoch of the Spanish civil war is checked. She investigated about children’s drawings during this confl ict and raised the possibility of using the drawings to evaluate the traumas of war, and she defended also the mediating value of drawing and painting between the child and his world, as element facilitator of the construction of sense.